Spatial distribution and speciation of sulfur in Ediacaran limestones with μ-XRF imaging and XANES spectroscopy: Implications for diagenetic mobilization of sulfur species. (1st August 2021) - Matsu'ura, Fumihiro; Nakada, Ryoichi; Usui, Tomohiro; Sawaki, Yusuke; Ueno, Yuichiro; Kajitani, Iori; Saitoh, Masafumi
Highlights: Shibantan limestone contains maximum 1237 ± 315 ppm of organic sulfur. Iron limitation enhanced organic matter sulfurization in Shibantan limestone. Microbial activity induced large CAS content variation in Shibantan limestone. CAS content decreased during marine and meteoric diagenesis. Organic sulfur content in limestone matrix decreased during marine diagenesis. Abstract: The Ediacaran period was characterized by numerous events, including the emergence of large multi-cellular metazoans and surface environmental perturbations. This period was also characterized by an increase in atmospheric oxygen concentrations that was critical for the evolution of life. Oceanic sulfate concentrations varied in association with atmospheric oxygen concentrations, which have been constrained by sulfur isotopic compositions of sedimentary sulfates and pyrite, and sulfur concentrations of pyrite and carbonate associated sulfate (CAS). However, other parameters such as sedimentation rate or iron availability have a strong impact on the abundance and isotopic composition of pyrite. In addition, recent studies have demonstrated that some Phanerozoic limestones include a mix of various carbonate minerals, the compositions and diagenetic histories of which differ at the μm scale. Thus, the μm scale description of sulfur species is necessary to accurately extract information preserved in carbonate rocks. In this study, we investigated the speciation and concentrations of sulfur in the matrix of the Ediacaran Doushantuo and Dengying limestones exposed in South China using μ-X-ray fluorescence (XRF) mapping and S K-edge X-ray absorption near edge structure (XANES) analyses. In addition to pyrite, the XANES spectra of the Doushantuo limestone indicate that sulfur occurs as CAS, while the Dengying limestone contains CAS and abundant organic sulfur. Pyrite oxidation and re-mineralization of organic sulfur had little influence on CAS content in the samples, whereas sparitization produced decreases in CAS and organic sulfur concentrations. The CAS content of the Dengying sparite was lower than that of the Dengying micrite, indicating that the CAS content decreased even during marine diagenesis. Thus, the micrite is more appropriate for extracting paleo-oceanic information. On the other hand, variations in the CAS concentrations of the limestone matrix in the Dengying Formation were larger than those in the Doushantuo Formation, regardless of grain size. The large variations in the Dengying limestone resulted from local alkalinity fluctuations caused by temporal changes in microbial activity within microbial mats. Existence of abundant organic sulfur in the Dengying limestones has another implication to ancient sedimentary environment. The low pyrite content of the Dengying limestone is likely due to a deficient supply of reactive iron to the sediment–water interface, because the supply of organic matter was likely sufficient.